Hybrid microwave power amplifiers for broadband communication / Pragash Sangaran - Pragash , Sangaran (2020)
The software-defined radio is the future of radio technology. The development of a broadband power amplifier is the most challenging radio component to design in achieving software-defined radio goals due to the PA gain-bandwidth limitation. The distributed power amplifier (DPA) overcomes the limitation by combining output power from several transistors in an additive fashion. Matrix Amplifier (MA) consists of two or more DPA stacked together in a multiplicative manner. In this project, a high power and high gain DPA for a two-way radio system is demonstrated. The DPA exhibits 10W output power and 32dB gain across the frequency range of 100MHz to 2GHz. The DPA also has an adjustable inter-stage matching cascaded network. A good correlation between measurement and simulation has been achieved. Simulation guidelines to achieve a good correlation between measurement and simulation are also given in this work. On top of that, the design of a high gain silicon BJT and E-pHEMT hybrid matrix amplifier with novel optimum filter matching technique is demonstrated. Conventional DPA and MA design techniques are only suitable for MMIC implementation because the availability of arbitrary values of lumped element Lc, Ld, Lb, and Cadd is only possible in MMIC technology. Therefore, a novel hybrid MA design and implementation methodology using novel optimum filter matching techniques are demonstrated. In this work, MA exhibits an average gain of 37.5 dB and an average Pout of 18 dBm in the band 0.65-5.8 GHz with 3V supply voltage. The gain is the highest among the state-of-the-art devices in the same frequency range. The bandwidth is 5.15 GHz, and P1dB is 20.3 dBm at 1.35 GHz. The PAE ranges from 10 % to 16 %, and Pdc is 1.2 W.